Effects of adjunctive brexpiprazole on sleep-wake and circadian parameters in youth with depressive disorders: study protocol for a clinical trial. Issue 9 (6th September 2022) - Carpenter, Joanne S; Zmicerevska, Natalia; Crouse, Jacob J; Nichles, Alissa; Garland, Alexandra; Song, Yun Ju Christine; Wilson, Chloe; Rohleder, Cathrin; McHugh, Catherine; Leweke, F. Markus; Koethe, Dagmar; Scott, Elizabeth M; et al.
Abstract : Introduction: Sleep-wake and circadian disturbance is a key feature of mood disorders with a potential causal role and particular relevance to young people. Brexpiprazole is a second-generation antipsychotic medication with demonstrated efficacy as an adjunct to antidepressant treatment for major depressive disorder (MDD) in adults, with preliminary evidence suggesting greater effectiveness in subgroups of depressed patients with sleep disturbances. This clinical trial aims to evaluate the relationships between changes in sleep-wake and circadian parameters and changes in depressive symptoms following adjunctive brexpiprazole treatment in young adults with MDD and sleep-wake disturbance. Methods and analysis: This study is designed as a 16 week (8 weeks active treatment, 8 weeks follow-up) mechanistic, open-label, single-arm, phase IV clinical trial and aims to recruit 50 young people aged 18–30 with MDD and sleep-wake cycle disturbance through an early intervention youth mental health clinic in Sydney, Australia. At baseline, participants will undergo multidimensional outcome assessment and subsequently receive 8 weeks of open-label treatment with brexpiprazole as adjunctive to their stable psychotropic medication. Following 4 weeks of treatment, clinical and self-report measures will be repeated. Ambulatory sleep-wake monitoring will be conducted continuously for the duration of treatment. After 8 weeks of treatment, all multidimensional outcome assessments will be repeated. Follow-up visits will be conducted 4 and 8 weeks after trial completion (including sleep-wake, clinical and self-report assessments). Circadian rhythm biomarkers including salivary melatonin, cortisol and core body temperature will be collected during an in-lab assessment. Additionally, metabolic, inflammatory and genetic risk markers will be collected at baseline and after 8 weeks of treatment. Ethics and dissemination: This trial protocol has been approved by the Human Research Ethics Committee of the Sydney Local Health District (X19-0417 and 2019/ETH12986, Protocol Version 1–3, dated 25 February 2021). The results of this study, in deidentified form, will be disseminated through publication in peer-reviewed journals, scholarly book chapters, presentation at conferences and publication in conference proceedings. Trial registration number: ACTRN12619001456145.